Carter - Schiff, David (Master musicians series., 2018)
This text surveys the life and work of the great American composer Elliott Carter (1908-2012). It examines his formative, and often ambivalent, engagements with Charles Ives and other 'ultra-modernists', with the classicist ideas he encountered at Harvard and in his three years of study with Nadia Boulanger in Paris; and with the populism developed by his friends Aaron Copland and Marc Blitzstein in Depression-era New York, and the unique synthesis of modernist idioms that he began to develop in the late 1940s.